The Relationship Between Metalinguistic Awareness & Linguistic Redundancy, Some Notes for Turkish Instructors - Alpaslan Okur; Seda Demir (Sakarya University Journal of Education)
Abstract. Pleonasm has been defined as a hypernym (umbrella term) in Western linguistics, mainly as an unnecessary language element, with expressions that can be translated as 'linguistic redundancy and extension or linguistic redundancy'. It is used to describe any element, component, or situation that contains semantic or functional repetition in the discourse that is not necessary for its function in any element belonging to any field of linguistics. Such an increase in the number of elements does not affect or change the intended meaning of the discourse and does not provide information that was not presented before. At the same time, the phenomenon in question serves some literary, phraseological, or pragmatic purposes, that is, it is used to create linguistic, poetic, and literary effects. However, the phenomenon in question may have some effects that make it difficult to understand the discourse in foreign language/second language learning. In developing metalanguage awareness, it is essential to present these elements to learners in the foreign/second language teaching process, intuiting and direct teaching. In developing metalanguage awareness, it is important to present these elements to learners in the foreign/second language teaching process, intuiting and direct teaching. The study was designed with a case study, which is a qualitative research design, and the data obtained in the research were subjected to content analysis and descriptive analysis. The problem of the study is to examine whether the learners of Turkish as a foreign language can identify examples of linguistic redundancy and extension in the discourse through their productive language skills, examine why these uses occur, and offer some suggestions to the instructors at the point of developing metalanguage awareness.